Analytical solutions for nonlinear long-short wave interaction systems with highly complex structure - Baskonus, Haci Mehmet; Bulut, Hasan; Belgacem, Fethi Bin Muhammad (Elsevier Science Bv, 2017)
In this paper, we investigate and use the new modified exp(-Omega (xi))-expansion method, (MEM). We apply the new MEM to nonlinear long-short-wave interaction systems (NLSWIS). Among our findings are sets of solutions including, but not limited to, new hyperbolic, complex, and dark soliton solutions. Not only is MEM shown to be highly adaptable for partial differential equations with strong nonlinearities, but also, it turns out to be highly efficient, despite its ease. (C) 2016 Elsevier B.V. All rights reserved.
International Conference on Mathematical and Computational Modelling in Science and Technology -- AUG 02-07, 2015 -- Izmir Univ, Izmir, TURKEY
Keywords: Complex hyperbolic solution; Dark soliton solution; Hyperbolic function solution; Long-short-wave interaction system; Modified exp(-Omega (xi)-expansion method